Inferior vana caval filter. Experience from a community hospital - Mian Muhammad Rizwan; Gurdeep Chhabra; Nigussie Geleta; Rabina Rai; Ankur Mishra; Linda Green (Mediterranean Journal of Hematology and Infectious Diseases)
Venous thromboembolism is a significant cause of morbidity and mortality. When pharmacological therapy fails or is contraindicated, interruption of the inferior vena cava (IVC) is recommended. We aim to audit our experience with both permanent and retrievable IVC filter placement at Prince George’s Hospital and compare them with establish guidelines. A retrospective single center audit of medical records for IVC filter placement was performed in consecutive patients from January 2007 to December 2010 (208 weeks). A total of 236 patients were identified as having IVC filter placed during the study period including 54.7% male (n=129) and 45.3% female (n=107). The mean age was 60.8 years. Of the 236 filters inserted, 32.8% (n= 65) were retrievable and 67.2% (n=133) were non retrievable. The most commonly inserted non-retrievable filter was Greenfield 65.7% (n=130), while G2 filter was the commonest retrievable filter constituting about 23.2%(n=46) of study population. 8.2% (n=19) of our patients had peri-procedure death. Of the 65 retrievable filters inserted during the study period, no    attempt for retrieval was made during same hospitalization in any patient. We conclude that IVC filters are highly effective in preventing PE related death but careful patient stratification is needed. The use of retrievable filters has not resulted in increased filter retrieval. Structured follow-up after retrievable filter placement can improve chances of retrieval.